PRELIMINARY STUDY ON POTENCY OF COPROSTANOL AND COLIFORM BACTERIA IN SEMARANG COASTAL AREA - Tonny Bachtiar (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Fecal coliform bacteria have been widely used as a biological indicator of sewage (domestic waste) pollution. However, as a biological indicator in urban coastal waters, it has disadvantage, in particular because of increased volume of industrial wastes that are toxic and heated, increase of salinity, and low dissolved oxygen. These conditions may affect the growth rate of most bacteria, including fecal coliform bacteria that becomes under representative in sewage pollution  in urban coastal waters. It is necessary to find alternative indicator that can be used to better understand the sewage pollution in urban coastal waters. Many researchers have proposed coprostanol as a chemical indicator of sewage pollution. To understand the existence of coprostanol and coliform bacteria, a preliminary study has been done on water and sediment samples from the river, river mouth, and seawater of Banjir Kanal Timur Semarang coastal waters. The results showed that coprostanol could be detected in sediment from all sites, on the other hand coliform bacteria decreased with the increase of salinity, and were not detected in the seawater.